Stability for Caputo Fractional Differential Systems - Sung Kyu Choi; Bowon Kang; Namjip Koo (Abstract and Applied Analysis)
We introduce the notion of h-stability for fractional differential systems. Then we investigate the boundedness and h-stability of solutions of Caputo fractional differential systems by using fractional comparison principle and fractional Lyapunov direct method. Furthermore, we give examples to illustrate our results.